Could polyhexanide and chlorine dioxide be used as an alternative to chlorhexidine? A systematic review - Santos, Paulo Sérgio da Silva (2022)
BACKGROUND: Maintenance of oral microbiota balance is the simplest way to prevent infectious oral diseases, through controlling dental biofilm. Combined use of mouthwash and mechanical removal has been shown to be a very effective way for this. OBJECTIVES: To identify clinical studies comparing the antimicrobial effect and possible adverse effects and/or side effects of chlorhexidine-based mouthwashes with those of mouthwashes containing chlorine dioxide and/or polyhexanide, for controlling oral microbiota. DESIGN AND SETTING: Systematic review designed by the stomatology sector of postgraduation in applied dental sciences of Bauru Dentistry School, University of São Paulo, Brazil. METHODS: A systematic review was conducted using online databases (PubMed, Embase, Web of Science and Science Direct) up to April 8, 2020. The search was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. RESULTS: The studies included comprised eight articles published between 2001 and 2017. A total of 295 young adults, adults and elderly people were evaluated (males 44.75% and females 55.25%). Three articles compared polyhexanide with chlorhexidine and five articles compared chlorine dioxide with chlorhexidine. No studies comparing all three mouthwashes were found. The concentrations of the study solutions were quite varied, and all rinses had an antimicrobial effect. In four studies, it was stated that no side effects or adverse effects had been found. Three studies did not address these results and only one study addressed side effects and/or adverse effects. CONCLUSION: Mouthwashes containing chlorine dioxide and polyhexanide are viable alternatives to chlorhexidine, since they reduce oral biofilm and have little or no reported side or adverse effects. SYSTEMATIC REVIEW REGISTRATION: PROSPERO - CRD42019115929 – Available from: https://www.crd. york.ac.uk/prospero/display_record.php?ID=CRD42019115929.